Decoding of communication signals for coexisting applications - Li, Yanyuan (Nanyang Technological University, 2020)
The popularity of personal mobility devices (PMDs) increases tremendously in recent years. PMDs are indispensable equipment for some elderlies and disables. In accordance with safety concern, it is strongly recommended PMDs to be equipped with distance measurement system and communication system. Hence, these measurements will be beneficial to both applications. In this project, we study the performance of communication system, radar transmission system and the coexistence of these two systems using MATLAB simulation. In communication system, quadrature phase-shift keying (QPSK) modulation techniques were applied to generate the bit error rate. In radar transmission system, a monostatic radar was implemented to estimate the target range. The coexisting application is the consolidation of communication system and radar transmission system. Various technique that aids in removing the interference are applied to study bit error rate (BER) performance.